MENINGKATKAN PARTISIPASI GENERASI MUDA DALAM DEMOKRASI: SOSIALISASI DAN PENDIDIKAN PEMILIH PADA PILKADA JAWA TIMUR 2024 - Muthowif Muthowif; Siti Lailatus Sofiyah; Moh. Ainul Fais; Wiwik Prihartanti; Mahardani Febrihapsari; Desak Gede Suasridewi (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2025)
The participation of millennials and Gen Z or often called the younger generation in the 2024 election has a crucial role in maintaining the legitimacy and quality of the election. Low political literacy, understanding of the rights and obligations as voters, and apathy are the main challenges in increasing the participation of young voters in the 2024 East Java Pilkada. Voter Socialization and Education activities organized by the East Java DPD Poros Sahabat Nusantara (POSNU) in collaboration with the East Java KPU aim to increase the political awareness of the young generation through an interactive approach. The methods applied include seminars, discussions, and question and answer sessions held in the W.R. University Hall. Supratman Surabaya. The results of the activity showed an increase in participants' understanding of the importance of their role in democracy, with high enthusiasm during the discussion. In addition, this activity makes a real contribution to efforts to increase young voter participation by providing in-depth insight into the election process and its impact on government policy. It is hoped that this activity can encourage the younger generation to become intelligent, critical and responsible voters in choosing leaders with integrity.